Mining the Genome of Streptomyces leeuwenhoekii: Two New Type I Baeyer–Villiger Monooxygenases From Atacama Desert - Gran-Scheuch, Alejandro; Trajkovic, Milos; Parra, Loreto; Fraaije, Marco W. (Frontiers in Microbiology, 2018)
Actinobacteria are an important source of commercial (bio)compounds for the biotechnological and pharmaceutical industry. They have also been successfully exploited in the search of novel biocatalysts. We set out to explore a recently identified actinomycete, Streptomyces leeuwenhoekii C34, isolated from a hyper-arid region, the Atacama desert, for Baeyer-Villiger monooxygenases (BVMOs). Such oxidative enzymes are known for their broad applicability as biocatalysts by being able to perform various chemical reactions with high chemo-, regio- and/or enantioselectivity. By choosing this specific Actinobacterium, which comes from an extreme environment, the respective enzymes are also expected to display attractive features by tolerating harsh conditions. In this work, we identified two genes in the genome of S. leeuwenhoekiii (sle_13190 and sle_62070) that were predicted to encode for Type I BVMOs, the respective flavoproteins share 49 % sequence identity. The two genes were cloned, overexpressed in E. coli with phosphite dehydrogenase as fusion partner and successfully purified. Both flavin-containing proteins showed NADPH-dependent Baeyer-Villiger oxidation activity for various ketones and sulfoxidation activity with some sulfides. Gratifyingly, both enzymes were found to be rather robust by displaying a relatively high apparent melting temperature (45 °C) and tolerating water-miscible cosolvents. Specifically, Sle_62070 was found to be highly active with cyclic ketones and displayed a high regioselectivity by producing only one lactone from 2-phenylcyclohexanone, and high enantioselectivity by producing only normal (-)-1S,5R and abnormal (-)-1R,5S lactones (ee >99 %) from bicyclo[3.2.0]hept-2-en-6-one. These two newly discovered BVMOs add two new potent biocatalysts to the known collection of BVMOs.